GW24-e2231 The dynamic change of dendroapsis natriuretic peptide (DNP) contents both in the plasma and left ventricle (LV) of spontaneously hypertensive rats (SHR). (1st October 2013) - Ying, Chen; Xiao-hong, Lin; Guang-rong, Zou; Ai-mei, Lin; Ying, Wu; Hua-shan, Hong
Abstract : Objectives: To evaluate the dynamic change of DNP contents both in the plasma and LV of SHRs and to explore the role of DNP in the development of hypertension and left ventricular hypertrophy (LVH). Methods: Male SHRs were served as experimental group, and were randomly divided into the following subgroups 4 weeks, 8 weeks, 12 weeks and 18 weeks group (n = 8), Male and age matched wistar kyoto rats (WKY) were as control group respectively (n = 8). Blood pressure was measured by tail-cuff plethysmography. Left ventricular mass index (LVMI) was calculated. The expression and distribution of DNP on LV were evaluated with immunohistochemical staining. The contents of DNP in both plasma and LV were measured with ELISA. The mRNA of DNP in LV was assessed Real- time PCR. Results: The SBP of SHRs was increased with ageing (highest at 18 weeks) ( P < 0.05). There was no obvious difference between SHRs and WKYs at 4 week on SBP ( P > 0.05), but SHRs showed higher SBP than WKYs at other three subgroups respectively ( P < 0.05). The LVMI of SHRs was increased with ageing ( P < 0.05). Futhermore, SHRs showed higher LVMI than WKYs at each subgroups ( P < 0.05). The concentration of DNP in plasma of SHRs was increased with ageing ( P < 0.01). The content of DNP in plasma of each subgroup of experimental group was higher than that in each subgroup of control respectively. ( P < 0.01). The expression of DNP on LV and its content changes: Immunohistochemical staining showed that DNP in LV was mainly distributed in the myocardial cells, endocardial endothelial cells, artery endothelial cells and artery smooth muscle cells. The expression of DNP on LV both in SHR and WKY rat was decreased gradually ( P <0.05). Furthermore, the expression of DNP on LV in each SHR subgroup was lower than that in WKY subgroup respectively ( P < 0.05). The content of DNP in LV was decreased with ageing both in SHRs and WKYs ( P < 0.05); each SHR subgroup of DNP in LV was lower than that in the WKY subgroup ( P < 0.05). The mRNA transcription of DNP was decreased with ageing in both SHRs and WKYs ( P < 0.05). Furthermore, each SHR subgroup was lower than that in the WKY subgroup ( P < 0.01). Conclusions: Results showed that the concentration of DNP in plasma of SHR was gradually increased with ageing, which may play a role in the development of hypertension. The date suggested that the expression of DNP on LV of SHR was gradually decreased with ageing, which may related to the development of LVH.